3-Degree-of-freedom electromagnetic vibration energy harvester with serially connected leaf hinge joints. (January 2019) - Kim, Hyun Soo; Ryu, Wooseok; Park, Shi-baek; Choi, Yong Je
This article presents a new design method of a planar 3-degree-of-freedom serial manipulator-type electromagnetic vibration energy harvester in which any desired ratio of power peaks and three target resonant frequencies can be specified arbitrarily. The design of the harvester aims to achieve minimum difference between the power peaks generated at target frequencies. The geometrical positions of three normal modes are first determined and the corresponding stiffness matrix of the harvester is found. Second, the stiffness matrix can be synthesized by three serially connected torsional springs. Third, the leaf hinge joints corresponding to torsional springs are designed using the newly developed design equations. Finally, the array and the locations of the magnets are found using the sequential quadratic programming (SQP) algorithm. The experiments are conducted to verify the design method. Three resonant frequencies are measured at 23.4, 29.2, and 34.8 Hz comparing to the target frequencies of 25, 30, and 35 Hz. The peak powers of 1.28, 0.89, and 1.32 mW are obtained across the optimal load resistor of 1.01 kΩ under the condition of the constant acceleration of 1.5 m/s 2 .